Investment in land – strategic decision - Novotný, Josef; Myšková, Renáta (Masarykova univerzita, 2019)
Nowadays, there is a significant loss of arable land both on a global and national scale and that is why this production factor is becoming an interesting investment tool for the investor public also in the Czech Republic. A problem that occurs in the Czech market environment is the lack of knowledge of the issues related to the investment plans into this asset by the domestic as well as foreigner investors and the uncertainty in the decision-making and the assessment on how strategically profitable it is to own land. The article points out the investment opportunities in land in real form and disadvantages of land ownership resulting from valid legislation of the Czech Republic and from the supply and demand in the land market. The key attributes that encourage the interest in this asset by the investors and speculators are described, and it is shown, using model examples, how the current legislative and market conditions reflect in the price of land and if it is strategically appropriate for the landowners to keep the land or sell it. Given the fact that the Czech investor environment has an absolute lack of finance index of this asset, a methodology of land index creation is designed.
Investování do půdy - strategická příležitost
Keywords: Land; investment; Finance index; investor; production factor; Půda; investice; finanční index; investor; výrobní faktor